The efficacy of sulphate quinine compared to fansidar in treating falciparum malaria in children 6 months – 7 years old - M. Mogi; T. H. Rampengan (Paediatrica Indonesiana, 1991)
From January 1989 until February 1990, 65 children suffering from falciparum malaria without complikation at the Department of Child Health Medical School Sam Ratulangi University/Gunung Wenang Hospital Manada were randomly allocated into 2 groups. The first group was treated with sulphate quinine based on the dose of 30 mg/kgbw/day in 3 divided doses and the other one was treated with single dose fansidar (sulphadoxine-pyrimethamine) based on the dose of sulphadoxine 20-30 mg/kgbw/day. The group treated with quinine showed much shorter duration of parasitemia compared with the group treated with fansidar. Fever subsided more rapidly in children treated with quinine compared with those treated with fansidar.